Struggle Of Oliver In Dickens’ Oliver Twist - Tini Mogea (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to learn about Oliver Twist's struggles. This research is qualitative, in which the data are in the form of words rather than numbers. The data were collected from the novel, with Oliver Twist as the primary source, and other books that were relevant to this topic. The result shows Oliver was suffering, but he never gave up; instead, he ran away and looked up a lover in London. in his struggle for survival. Oliver shows his hard work in the orphanage and tries hard to break the rule or regulation. Oliver Twist is the first person to speak out against orphan mistreatment in the infant farm, where orphans would go for several nights without food. Oliver is very brave and never afraid of anyone, even though he is still a child. Never think that the world is full of bad people; good people are all around; they embellish good thoughts, nurture fine souls, and welcome you with an open heart. Their positive personality traits have a great impact on lives, and their influences are far stronger and more everlasting. When Mr. Brownlow resolves to save innocent Oliver Twist, nothing can stop him from rescuing the boy. It is also because of Oliver’s pure and good heart.